2019
DOI: 10.15414/jmbfs.2019.8.4.989-994
|View full text |Cite
|
Sign up to set email alerts
|

PRODUCTION AND PHYSICOCHEMICAL PROPERTIES OF THERMOSTABLE, CRUDE CELLULASE FROM ENTEROBACTER CLOACAE IP8 ISOLATED FROM PLANT LEAF LITTERS OF LAGERSTROEMIA INDICA Linn.

Abstract: Cellulases have wide applications and biotechnological potentials for various industries. A bacterium producing an extracellular, thermostable cellulase was isolated from plant leaf litters of Lagerstroemia indica Linn, inside a botanical garden. According to morphological, biochemical and physiological characterization, it was tentatively identified as Enterobacter sp. Molecular characterization, using the 16S rRNA gene sequencing was used to confirm the identity of the bacterium as Enterobacter cloacae IP8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
3
4
1
Order By: Relevance
“…Fe 2+ , Mn 2 , and Cu 2+ caused a decrease in the cellSNSY enzyme activity. These results agreed with the results obtained by many researchers [ 57 59 ], who reported that both Ca 2+ and Na + cations exhibited stimulatory effects on the enzyme activity in all tested concentrations. The results of the under investigation are in agreement with Asha et al [ 40 ] who reported for the activity of the purified cellulase from Paenibacillus barcinonensis which is stimulated in the presence of metal ions such as Mg 2+ , Mn 2+ , and Co 2+ .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Fe 2+ , Mn 2 , and Cu 2+ caused a decrease in the cellSNSY enzyme activity. These results agreed with the results obtained by many researchers [ 57 59 ], who reported that both Ca 2+ and Na + cations exhibited stimulatory effects on the enzyme activity in all tested concentrations. The results of the under investigation are in agreement with Asha et al [ 40 ] who reported for the activity of the purified cellulase from Paenibacillus barcinonensis which is stimulated in the presence of metal ions such as Mg 2+ , Mn 2+ , and Co 2+ .…”
Section: Discussionsupporting
confidence: 93%
“…Also, Chai et al [ 22 ] found that the cellulase activity was increased by Mn 2+ , Ca 2+ , Zn 2+ , and Mg 2+ at 1 mM. In contrast to ones’ results, Akintola et al [ 57 ] reported that Mg +2 inhibited the activity of cellulase from Enterobacter cloacae IP8 at concentration 4 mM to 15 mM; it stimulated its activity at concentrations (ranged 20–200 mM). Gong et al [ 49 ] noticed that the recombinant Cel14b22 was considerably enhanced by Mn 2+ , but intensely reduced by Fe 3+ or Cu 2+…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results coincide with those reported for S. marcescens strain where cellulase production acts as primary metabolite, since it occurs from cell growth stage to the end of exponential stage or beginning of stationary stage [50]. Regarding bacteria of genus Enterobacter, the bibliography indicates that this relationship is strain dependent [51,52].…”
Section: Discussionsupporting
confidence: 88%
“…Cellulose chemically consists of several β-glucose subunits linked by β-1,4-glucosidic bonds. Cellulases break the bonds of this molecule [ 8 , 9 ]. The intermolecular bonds of cellulose create a particularly very tough crystalline molecule; therefore, the cellulolytic activity requires multiple complex enzyme systems for enzymatic hydrolysis, requiring the synergistic action of endo-glucanase, exo-glucanase, and glucosidase enzymes that degrade cellulose converting the products into a usable energy source [ 1 ].…”
Section: Introductionmentioning
confidence: 99%